2011
DOI: 10.7205/milmed-d-10-00336
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Cannabis Consumption in the French Army: Determination of Consumer Profiles to Focus on Prevention and Care

Abstract: Our results favor targeting the youngest to prevent the risks of high alcohol intake and cannabis consumption and addiction linked to repeated binge drinking. Systematic questionnaires on consumption habits and addiction self-evaluations during medical consultations could lead to early care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We have previously reported that the prevalence of hazardous alcohol use and smoking in this sample are less than that reported in US and UK military personnel [ 19 ]. Prevalence of cannabis use too is less than that reported among French, Canadian, Brazilian and Somalian military personnel [ 13 16 ]. Prevalence of probable PTSD was 1.9 % in the Special Forces and 2.7 % in the regular forces [ 19 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We have previously reported that the prevalence of hazardous alcohol use and smoking in this sample are less than that reported in US and UK military personnel [ 19 ]. Prevalence of cannabis use too is less than that reported among French, Canadian, Brazilian and Somalian military personnel [ 13 16 ]. Prevalence of probable PTSD was 1.9 % in the Special Forces and 2.7 % in the regular forces [ 19 ].…”
Section: Discussionmentioning
confidence: 91%
“…Prevalence of cannabis use among military populations vary. In the French army 18.5 % reported using cannabis at least once in the past 12 months and 8.1 % reported regular use (smoking at least 10 joints per month) [ 13 ]. Among Canadian Forces 14 % reported cannabis use [ 14 ].…”
Section: Introductionmentioning
confidence: 99%